Pengujian UV-Proteksi Ekstrak Metanol Daun Jeruk Purut (Citrus hystrix) secara In Vitro - Afni; Angga; Risna Agustina (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2019)
Kaffir Lime leaves (Citrus hystrix) often used for various treatments and also for cosmetics. One of the benefits of lime leaves in cosmetics is Sunscreen. The purpose of this study is to determine the activity of sunscreen and the category of sunscreen. The value %Te, %Tp, and Spf can be seen from the results of the calculation. The method is used by maceration. Then, the measurements using an UV spectrophotometer. At concentration of 100 ppm, 200 ppm, 300 ppm, 400 ppm and 500 ppm. At wavelengths of 292,5 - 372,5 nm for measurements of values % Te and % Tp. While for SPF values at wavelengths of 290 - 320 nm. The best results obtained were at concentration of 500 ppm, with a value of % Te 1,78 which is an extra protection category and the value of % Tp 1,27 which is the sunblock category, and the value of SPF 16 which is the ultra category.